2019
DOI: 10.52131/jom.2019.0102.0007
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Health Consciousness and Obesity Perception with Purchase Intention for Coca Cola Pakistan

Abstract: In the vilest competitive market, the purchaser goods manufacturing industries pay devotion to purchasing intention to continue their market status and boost their goodwill. This research study was agreed out to clarify the factors affecting the purchase intention of Coca Cola. This study aims to observe the effect of the independent variable (Health Consciousness and Obesity perception) on the dependent variable (purchase intention). The study describes that the relation between the dependent variable has an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In general, previous research has found that health consciousness has positive and significant effect on customers' purchase intention toward herbal products, supplements, and organic and green products (Widyaningtyas et al, 2023;Handayani & Darmawan, 2022;Wahab & Tajuddin, 2020;Parashar et al, 2023;Damberg, 2022;Shah et al, 2021;Tan et al, 2019). Meanwhile, some researchers fail to find the significant effect of health consciousness on customers' purchase intention toward herbal products, supplements, and organic and green products (Sultan et al, 2019;Asteria & Hati, 2023;Echchad, 2023). Based on the description above, the following research hypothesis can be formulated.…”
Section: Introductionmentioning
confidence: 99%
“…In general, previous research has found that health consciousness has positive and significant effect on customers' purchase intention toward herbal products, supplements, and organic and green products (Widyaningtyas et al, 2023;Handayani & Darmawan, 2022;Wahab & Tajuddin, 2020;Parashar et al, 2023;Damberg, 2022;Shah et al, 2021;Tan et al, 2019). Meanwhile, some researchers fail to find the significant effect of health consciousness on customers' purchase intention toward herbal products, supplements, and organic and green products (Sultan et al, 2019;Asteria & Hati, 2023;Echchad, 2023). Based on the description above, the following research hypothesis can be formulated.…”
Section: Introductionmentioning
confidence: 99%